2020
DOI: 10.1111/ctr.14084
|View full text |Cite
|
Sign up to set email alerts
|

The impact of belatacept on the phenotypic heterogeneity of renal T cell–mediated alloimmune response: The critical role of maintenance treatment and inflammatory load

Abstract: The introduction of calcineurin inhibitors (CNIs) ushered a new era of renal transplantation by dramatically improving short-term allograft survival. 1,2 However, CNIs also became an additional contributor to late allograft loss due to their deleterious toxicity profile. 3 Since the late 1990s, there have been ongoing efforts to minimize CNI use or replace them with less toxic agents such as mycophenolate mofetil (MMF) with or without mechanistic target of rapamycin (mTOR) inhibitors and steroid. 4,5 The most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…There is an obvious link between belatacept and macrophages as this compound blocks CD80/86 co-stimulatory molecules on APCs, which also include macrophages [163]. A study of renal transplant biopsies from patients treated with either calcineurin inhibitor or belatacept indicated that co-stimulatory blockade with belatacept was positively associated with genes related to innate immune responses including receptors of phagocytes (e.g., CD16, CD14, CD68, CD209, and TLR4) [144]. However, the effect of belatacept on macrophages is not well investigated.…”
Section: Belataceptmentioning
confidence: 99%
“…There is an obvious link between belatacept and macrophages as this compound blocks CD80/86 co-stimulatory molecules on APCs, which also include macrophages [163]. A study of renal transplant biopsies from patients treated with either calcineurin inhibitor or belatacept indicated that co-stimulatory blockade with belatacept was positively associated with genes related to innate immune responses including receptors of phagocytes (e.g., CD16, CD14, CD68, CD209, and TLR4) [144]. However, the effect of belatacept on macrophages is not well investigated.…”
Section: Belataceptmentioning
confidence: 99%